Գեղարվեստավավերագրական բնագրերի բառապաշարի բառակազմական կաղապարները - Գալստյան, Ա․ Վ․
Исследуя язык художественно-документального жанра, замечаем, что широкое распространение имеют двухкомпетентные реальные сложности. В мемуарах часто используются шаблоны с конечными компонентами как տուն [tun], պետ [ {pet], մայր [mayr], հայր [hayr], հայ [hay], գիր [gir], սեր [ser], հանդես [handes] и др. Употребляются также слова данного исторического периода. Некоторые мемуаристы используют слова, типичные для определенных профессий. В языке мемуаров большое место занимают также сочетания. The study of the linguistic aspect of documentary-fiction genre has detected that the authentic texts of the subject-matter genre appear to contain in abundance units of bicomponent compounding proper. In the authentic texts of the memoir genre, the words with such final components as տուն [tun], պետ [ {pet], մայր [mayr], հայր [hayr], հայ [hay], գիր [gir], սեր [ser], հանդես [handes], etc. are high-frequency word-formation patterns.The lexical units typical of the given time are also recurrent. Some memoirs, due to the scope of professional or specific interests, contain professional terms of the sphere given. At the same time, the language of memoirs tends to contain reduplications in considerable proportion.
Keywords: Լեզվաբանություն